Representações do corpo estranho na ficção de Antônio Carlos Viana - Silva, Gisélia Mendes da (2011)
This research aims to investigate the role of the strange in the fiction of the short story writer Antônio Carlos Viana from Sergipe in the written works O meio do mundo e outros contos (1999), Aberto está o inferno (2004) and Cine privê (2009). These collections bring a set of strange beings to the family and the patriarchal society. The stranger in the fiction of Viana unbalances the rigorous standards of absolute truth and challenges the dead posture that leads people to live by the roots of a molded patriarchal system that, while outdated, is still adjusting behaviors. As theoretical and methodological subsidies, we used reflections of gender, body, sexuality and monstrosity studies. We go from the concept of strange as the one who has no definitions, rethinks the power and poisons the set standards, proposed by Zygmunt Bauman, Michel Foucault and Jacques Derrida; as the one who challenges and destabilizes the rules laid down as Guacira Louro, Elodia Xavier and Elizabeth Grosz, and finally as a metaphor of evil, proposed by Luiz Nazario, Jerome Cohen and Julio Jeha. We divide this essay into three chapters: in the first, Corpos marcados, we do a study of the strange of gender and analyze the stories O amor de Isa e Nane , Maria filha de Maria from the work Cine privê and Doutora Eva from Aberto está o inferno; the second, Do corpo à sexualidade, we rethink the no place of people that are broken down by sexual orientation and analyze the stories Eliazar, Eliazar , from Cine privê, Os mestres , Jardins suspensos and Meu tio tão só from O meio do mundo e outros contos; in the third, Monstruosidade nos corpos, we investigate the short stories Nadinha , Aos domingos from O meio do mundo e outros contos e Lofote e sua mãe from Aberto está o inferno. Of possession of such fictional material and theorical contributions, we seek to establish dialogue between the literary and social discourses and propose a space for debate in which social issues may be validated in the space of irreverent literary aesthetics.